2007
DOI: 10.1002/em.20292
|View full text |Cite
|
Sign up to set email alerts
|

Water soluble fraction of solar‐simulated light‐exposed crude oil generates phosphorylation of histone H2AX in human skin cells under UVA exposure

Abstract: Crude oil contains compounds, which have toxic and cancer-causing properties to humans. The oil spilled in environments is usually exposed to sunlight; however, the toxicity of sunlight-exposed oil is poorly understood. In this study, we found that the water soluble fraction (WSF) of crude oil irradiated with solar-simulated light (SSL) generated phosphorylation of histone H2AX (gamma-H2AX) in human skin cells under UVA irradiation, which was due to the formation of DNA double strand breaks (DSBs). Crude oil w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Induction of γ -H2AX is found following exposure of cells to suspected DNA-damaging compounds such as cigarette smoke, polycyclic aromatic compounds, dinitrobenzo[e] pyrene, norethindrone, chromium, crude oil, electromagnetic fields, microwaves from mobile phones, and extreme heat, all demonstrating a potential role for γ -H2AX detection in determining potential genotoxics (Albino et al 2004; Gallmeier et al 2005; Hunt et al 2007; Ibuki et al 2007; Kawanishi et al 2009; Luo et al 2006; Markova et al 2005; Mattsson et al 2009; Peterson-Roth et al 2005; Shao et al 2004; Toyooka and Ibuki 2005, 2006, 2009). The radiation induced bystander effect, which can be monitored through DSB induction, can also be tracked using γ -H2AX formation (Sokolov et al 2007).…”
Section: γ-H2ax As An Indicator Of Environmental Health Risksmentioning
confidence: 99%
“…Induction of γ -H2AX is found following exposure of cells to suspected DNA-damaging compounds such as cigarette smoke, polycyclic aromatic compounds, dinitrobenzo[e] pyrene, norethindrone, chromium, crude oil, electromagnetic fields, microwaves from mobile phones, and extreme heat, all demonstrating a potential role for γ -H2AX detection in determining potential genotoxics (Albino et al 2004; Gallmeier et al 2005; Hunt et al 2007; Ibuki et al 2007; Kawanishi et al 2009; Luo et al 2006; Markova et al 2005; Mattsson et al 2009; Peterson-Roth et al 2005; Shao et al 2004; Toyooka and Ibuki 2005, 2006, 2009). The radiation induced bystander effect, which can be monitored through DSB induction, can also be tracked using γ -H2AX formation (Sokolov et al 2007).…”
Section: γ-H2ax As An Indicator Of Environmental Health Risksmentioning
confidence: 99%
“…We previously reported that ␥-H2AX is generated following the exposure of cells to various suspected DNA-damaging agents including several environmental chemicals and pharmacological agents [20][21][22][23][24][25][26][27][28]. In addition to the advantage that ␥-H2AX can be detected in response to many types of DNA damage, we and other researchers are convinced that ␥-H2AX provides a considerably more sensitive measurement of DNA damage than other techniques such as pulse field gel electrophoresis and comet assays [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%